Semiotics Gothic Era in Cyprus - Atakara, Cemil; Doğu, Cem (ICONARCH International Congress of Architecture and Planning, 2017)
The main aim of this paper is to analyze Gothic Period in Cyprus during which cathedrals, churches, chapels were built in gothic style and also to discuss and analyze these gothic buildings according to the semiotic approach. Semiotic approach is silent language of buildings. Are forms and shapes most effective communication way between old memory of place? The main point of this research, create a relationship between physical, symbolic, spiritual memories and interpretation with gothic and contemporary building style. Contemporary designs and techniques have provided different effects and space feelings on users. But acutully there are many similaritys between gothic and contemporary architectural designs. In addition, this paper focuses on structural, climatical, spatial organization and ornamentals through semiotics theory and deals with transparency approaches with selected buildings. The limitations of this text, however, is the restriction in the focus among a wide range of parameters offered by the semiotics theory by taking only one gothic styles among many into consideration as they reflect semiotic theories level. Semiotic theory is a very broad concept and semiotic approach deals with main ideas which signify some signs of other ideas or elements for people. Considering the fact that each element or text signify some ideas, theories, elements or some results, sign-object relations create semiotic theory. The method of research used in this paper is a qualitative one and it is prepared by using varied reference from books, magazines, texts to drawings regarding gothic architecture. Thirty six different gothic style buildings, which were built in Cyprus, have been anaylzed and all buildings are grouped in 3 categories according to the semiotic approach. In conclusion, when gothic style buildings are analyzed architecturally in Cyprus, numerous similarities could be drawn between them and the contemporary architecture. As mentioned before, semiotic theory and approach is very effective on sign-object relations, since each architectural element or system is considered to be a sign and reference for contemporary architecture.